2007
DOI: 10.1007/s10554-007-9283-z
|View full text |Cite
|
Sign up to set email alerts
|

MRI of great vessel morphology and function in Ehlers-Danlos syndrome type IV

Abstract: The purpose of this study was to investigate whether large arteries in subjects with Ehlers-Danlos Syndrome Type IV (EDS IV) exhibit altered morphological and functional characteristics that might indicate the risk of complications. Subjects with EDS IV, an inherited disorder of type III collagen, have a significant lifetime risk of arterial rupture. Magnetic Resonance Imaging (MRI) of the aorta and carotid artery was used to measure diameter, wall thickness, pulse propagation velocity, and spin-spin relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Both these reports illustrate the use of structural data in the interpretation of genomic and sequence variants in human disease. With regard to missense variants in the C‐propeptide of COL3A1 , in addition to those presented here and already discussed [Bourhis et al, ], two variants have been found in the region of the Ca 2+ binding site (p.Gly1284Glu [Jørgensen et al, ]; p.Asp1288Val [Kerwin et al, ]), both of which affect trimerization leading to reduced amounts of procollagen III. Furthermore, another sequence variant (p.Pro1440Ser, similar to Patient 1) has also been reported [Morissette et al, ], though the biochemical consequences have not been described.…”
Section: Discussionsupporting
confidence: 66%
“…Both these reports illustrate the use of structural data in the interpretation of genomic and sequence variants in human disease. With regard to missense variants in the C‐propeptide of COL3A1 , in addition to those presented here and already discussed [Bourhis et al, ], two variants have been found in the region of the Ca 2+ binding site (p.Gly1284Glu [Jørgensen et al, ]; p.Asp1288Val [Kerwin et al, ]), both of which affect trimerization leading to reduced amounts of procollagen III. Furthermore, another sequence variant (p.Pro1440Ser, similar to Patient 1) has also been reported [Morissette et al, ], though the biochemical consequences have not been described.…”
Section: Discussionsupporting
confidence: 66%
“…In our study, PWV was considered as the distance between two points divided by the time needed for the pulse wave to cover this distance. Similar methods also using magnetic resonance imaging have previously been described (13,16,17,32,33). The principal difference between the proposed methods is the determination of the transit time for the flow wave to propagate from one point to another.…”
Section: Discussionmentioning
confidence: 99%
“…The vascular type of Ehlers-Danlos is a rare disease presenting as spontaneous arterial rupture usually without dissection (56). A small study using MRI showed that AD was reduced, whereas aortic wall thickness was slightly increased, although only 9 of 15 subjects had interpretable images (57). After aortic coarctation repair.…”
Section: Connective Tissue Disorders (Marfan Syndrome and Ehlers-danlmentioning
confidence: 99%